Prevalence, incidence and outcome of periodontal diseases among the elderly - Al Subait, Abeer Abdulrahman; Saidi, Khadijah Mustafa; Alsagoor, Hussain Hadi; Alrasheedi, Naif Mayouf; Alanazi, Asma Gadan; Alfattany, Redwan Jamalaldeen; Alshammari, Hatim Marzouq; Alshehri, Shahad Amer; Alfaifi, Asma Ali; Alosaimi, Omar Obaid; Samargandi, Azhar Abdullah (International Journal Of Community Medicine And Public Health, 2021)
When compared to adults, older persons have a higher prevalence and incidence of periodontal diseases. The prevalence of periodontitis is substantially greater in the geriatrics group, which is 75 years old on average, compared to those who are 60 years old on average. Periodontitis can lead to tooth loss if natural periodontal therapies are not used. Periodontitis is the sixth most frequent incurable illness in the world, characterized by bacterial-induced and host-mediated deterioration of both soft and hard structures around the teeth. A severe type of periodontitis affects around 10% of the world's population. Periodontitis is more frequent in adults because of its chronic and debilitating nature, with around 66% of the 65-year-old age group in the United States afflicted by chronic periodontitis. A critical component of a successful disease prevention and health promotion trajectory is having up-to-date information on demographics, clinical symptoms, and illness burden on individuals, particularly in underrepresented regions where preventive programs are targeted and executed. As a result, the purpose of this paper is to evaluate the existing research on the prevalence, incidence, and consequences of periodontal diseases in the older population.